Peran Orang Tua dalam Membangun Rumah Tangga pada Pasangan Pernikahan Dini Menuju Keluarga Sakinah di Desa Margoyoso Kecamatan Kalinyamatan Kabupaten Jepara - Rifqi Taufiqurrohman; Nabila Cahya Adinda; Setiyowati Setiyowati (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Early marriage is a social phenomenon that continues to thrive in Margoyoso Village, Kalinyamatan District, Jepara Regency, despite government regulations establishing a minimum age for marriage. Couples who marry at a young age are vulnerable to emotional and economic unpreparedness, which threatens the integrity of the household and the achievement of the goal of a harmonious family. This study aims to identify factors that encourage early marriage and describe the strategic role of parents in strengthening the resilience of these couples’ families. The research method used was descriptive qualitative, with data collection techniques including in-depth interviews and participant observation of couples and parents. The results indicate that early marriage in Margoyoso Village is influenced by family economic factors, low levels of education, and local cultural customs. Furthermore, the findings indicate that parents play a significant role in helping couples overcome marital crises through material support, psychological guidance, and parenting guidance. Parents serve as a balance when couples experience conflict and limited experience. The implications of this study emphasize that the success of early marriage does not depend solely on the couple, but is largely determined by the intensity of support and guidance provided by parents as part of an extended family system that upholds Islamic values.